PIBID e formação docente: contribuições do professor supervisor para a prática pedagógica do aluno egresso em início de carreira - Queiroz, Elaine de Oliveira Carvalho (2017)
This research aimed to analyze the contributions of the supervisor professor to the pedagogical practice of the Pedagogy graduating student at the beginning of their careers and that have taken part of the Programa Institucional de Bolsa de Iniciação à Docência (Pibid). The specific objectives are: to analyze whether the performance of the supervisor professor, during the time the project was ongoing, contributed to the professional development of the graduating students; to verify if the action of the supervisor professor contributed to the process of insertion in the teaching environment and if the relation between university and public schools, through Pibid, has favored the teachers’ initial education. Our hypothesis is that Pibid facilitates the connection between theory and practice in the graduation courses for teachers and, furthermore, that the participation of the supervisor professor during the education moments contribute to the professional education of the scholarship students. Therefore, we aimed to answer to following questions: What are the contributions of the supervisor professors for the professional development of the Pedagogy course graduating students that were part of Pibid and that are currently teaching? In what extent do the actions of the supervisor professors contributed to the professional insertion of the graduating students in their teaching? The context of this research was a private education institution in the south area in the city of São Paulo and the participants were six graduating students that were part of the Pibid and are currently teaching. It was a qualitative research, which had as data collecting instrument, at first, a closed form and, after, semi-structured interviews, besides the analysis of the official documents from Ministério da Educação (MEC) and the Coordenação de Aperfeiçoamento de Pessoal de Nível Superior (Capes), that give support to Pibid. The theoretical background was based in Critical Pedagogy authors, being them: Marcelo Garcia (2009, 2011, 2013), Tardif (2000, 2014), Canário (2000, 2001, 2007), Mizukami (2000, 2002, 2004, 2013), Nóvoa (1992, 1995, 2009), Shulman (1986, 2014, 2016), Gatti (2009, 2011, 2013, 2016) e Zeichner (1993,2010), in studies about the role of the teacher, teaching knowledges, the relation between theory and practice and teacher education. The data analysis was based on the Content Analysis by Bardin (2011). As a result, we noticed that, because of the actions of the supervisor teachers towards the scholarship students participating in the Pibid, a partnership was stablished between the university and the public schools, improving the education of the Pedagogy course students and allowing them to have better teaching practices. Students disclose the relation between theory and practice as being positive to the pedagogical practice, and emphasize the role of the supervisor teacher as agents in the process providing autonomy. However, it is noticed that this relation still happens in a vertical way instead of allowing a more challenging education process.